A new subgenus of Stigmatophora Staudinger, 1881 (Lepidoptera, Erebidae, Arctiinae, Lithosiini) from China, with descriptions of three new species - Lu Zhang; Tingting Zhao; Huilin Han (ZooKeys)
We describe three newly discovered species of the genus Stigmatophora Staudinger, 1881 from China, (S. bucseki sp. nov., S. longa sp. nov., and S. dianensis sp. nov.) and establish a new subgenus Bifurcistigma subgen. nov. for the first two. Detailed descriptions of the external morphology and male and female genitalia of the new species are provided, along with those of S. obraztsovi Daniel, 1951, which is also assigned to the new subgenus. A checklist of all species of Stigmatophora is presented including the distribution, type locality, and synonymy of each.